The design and control of mine refrigeration systems - Howes, Michael (1992)
The research is directed towards modelling the chiller set, the heat rejection and the load subsystems of a complete mine refrigeration system and simulating the performance in order that the design can be optimised and the most cost effective control system determined. The refrigeration load profile for a mechanised mine is complex and primarily a function of surface climatic variations, the strongly cyclic sources of heat resulting from the operation of diesel powered mining equipment and the associated differences in thermal environmental acceptance criteria.